2022
DOI: 10.3390/app12010465
|View full text |Cite
|
Sign up to set email alerts
|

The Complex of Experimental Facilities for the Cosmic Ray Investigation at the Tien Shan Mountain Station

Abstract: The study describes the experimental complex of the station located in the Tien Shan mountains at an elevation of 3340 m above sea level. The complex consists of detectors of different types scattered across the station area, such as scintillation particles detectors, Cherenkov detectors, radio emission detectors for the measurement of the electron component of extensive air showers (EAS) created by the (1–1000) PeV cosmic ray particles, an ionization calorimeter and neutron detectors for the study of the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is known [13,17] that one of the conditions for the occurrence of acoustic emission in the Earth's crust is the threshold energy of muons, which is 3 GeV. Muons of such energies arise under the condition that the energy of primary particles reaches 10 15 eV.…”
Section: The Discussion Of the Resultsmentioning
confidence: 99%
“…It is known [13,17] that one of the conditions for the occurrence of acoustic emission in the Earth's crust is the threshold energy of muons, which is 3 GeV. Muons of such energies arise under the condition that the energy of primary particles reaches 10 15 eV.…”
Section: The Discussion Of the Resultsmentioning
confidence: 99%
“…The dosimetric monitoring in these areas combines scientific interest aiming to deepen the knowledge of the physical aspects of cosmic radiation with the need to meet the requirements of radiation protection recommendations for human exposure. Many studies demonstrated that aircraft crew and astronauts constitute a group of workers receiving one of the highest annual effective doses [ 22 , 23 , 24 , 25 , 26 , 27 ]. Because of this scientific evidence, the International Commission on Radiological Protection (ICRP) stated that the exposure to cosmic radiation of aircraft crew and frequent flyers must be managed as a planned exposure situation in order to monitor the received dose and minimize the potential risk of radio-induced effects on health [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%